2022
DOI: 10.1073/pnas.2110329119
|View full text |Cite
|
Sign up to set email alerts
|

Pericyte dysfunction and loss of interpericyte tunneling nanotubes promote neurovascular deficits in glaucoma

Abstract: Reduced blood flow and impaired neurovascular coupling are recognized features of glaucoma, the leading cause of irreversible blindness worldwide, but the mechanisms underlying these defects are unknown. Retinal pericytes regulate microcirculatory blood flow and coordinate neurovascular coupling through interpericyte tunneling nanotubes (IP-TNTs). Using two-photon microscope live imaging of the mouse retina, we found reduced capillary diameter and impaired blood flow at pericyte locations in eyes with high int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 59 publications
1
36
0
Order By: Relevance
“…Pericytes are mural cells that wrap around the endothelial cells that line capillary blood vessels. A recent study has found reduced capillary diameter and impaired blood flow at pericyte locations in mouse eyes with high IOP 70 .…”
Section: Discussionmentioning
confidence: 94%
“…Pericytes are mural cells that wrap around the endothelial cells that line capillary blood vessels. A recent study has found reduced capillary diameter and impaired blood flow at pericyte locations in mouse eyes with high IOP 70 .…”
Section: Discussionmentioning
confidence: 94%
“…OHT was induced by intracameral injection of magnetic microbeads, which were attracted to the iridocorneal angle with a magnet to block aqueous humor outflow and increase intraocular pressure (Figures 1C and 1D) (Ito et al, 2016). Mitochondrial movement was evaluated at 2 weeks after microbead injection because (1) high intraocular pressure is stable but no significant RGC loss is detected (Figure S1A) (Ito et al, 2016;Belforte et al, 2021;Alarcon-Martinez et al, 2022), and (2) Thy1-mediated transgene and protein expression do not differ from naive retinas at this time point (Belforte et al, 2021), confirming stable Thy1 promoter activity. Mitochondrial transport in intraretinal RGC axons was visualized using two-photon laser scanning microscopy (TPLSM) (Figure 1E), allowing minimally invasive trans-scleral imaging of mitochondria with single-axon resolution in living mice (Figure 1F; Videos S1 and S2).…”
Section: Impaired Anterograde Axonal Transport and Mitochondria Deple...mentioning
confidence: 99%
“…The role of TNT at the blood-central nervous system barriers remains largely unknown. The role of interpericytes TNT (IP-TNT) in the regulation of neurovascular coupling under physiological conditions and their dysfunction in glaucoma were recently characterized in the mouse retina [ 33 , 41 ]. However, whether TNT play a role at human BBB-level remains unexplored.…”
Section: Discussionmentioning
confidence: 99%